Justyna Kobus: THE LEXIS OF THE NATURE SUBJECT FIELD IN GREATER POLAND’S DIALECTOLOGICAL RESOURCES - Kobus, Justyna (Linguistic Bulletin (Movoznavchyi Visnyk), 2022)
Аbstract. Introduction. The article discusses the achievements of Greater Poland’s dialectology in the field of documenting names related to untamed nature (wild). Purpose. The aim of the article is to discuss the results of the query of dialectological sources deposited in the Dialectological Laboratory of the University of Adam Mickiewicz in Poznań. The research scope included the lexis of the NATURE field. The author distinguished three groups of materials: the file of Adam Tomaszewski, data from the Atlas of the language and folk culture of Greater Poland, and contemporary materials obtained in order to develop the NATURE thematic volume as part of the Greater Poland’s Regional Dictionaries series. Results. Old materials allow for the development of several dozen headline articles from various parts of Wielkopolska. In the Atlas of the Folk Language and Culture of Greater Poland, 112 maps of nature have been developed. Contemporary research on this topic is only in its early stages. Orginality. The article is the first attempt to verify the resources of Greater Poland dialectological sources for the study of natural dialectal vocabulary. Conclusion. Due to the modest dialectological material base for the topic under study, the researcher recommends intensifying contemporary field research.